Assessing Poverty In Elderly Households: Empirical Evaluation And Policy Implications - Martha Carolina; Jesly Panjaitan (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
Indonesia is undergoing a demographic transition marked by a rising proportion of elderly populations, presenting significant challenges to its economic system and social welfare policies. This study aims to assess poverty levels among elderly households and examine key determinants, including education, health insurance coverage, social assistance programs, and household structure. Utilizing 2024 Susenas data and Probit regression analysis, the findings reveal that higher education and health insurance ownership significantly reduce the likelihood of elderly poverty. Conversely, participation in social assistance programs such as the Program Keluarga Harapan (PKH) and Atensi Lansia is positively associated with poverty status—indicating accurate targeting, yet also underscoring persistent economic vulnerability. Additionally, larger household sizes increase poverty risk, while a greater number of working household members reduces it. These results highlight the need for holistic policy interventions—particularly in education, social protection expansion, and economic empowerment for the elderly—to mitigate the impact of population ageing and build a more inclusive and sustainable social protection system.